4.2k views
5 votes
Question 1
Given: f(x)=x2-1 and g(x) = 2x-5
Find: (gof)(x)

User Cao
by
4.5k points

1 Answer

6 votes

Answer:


(g\circ f)(x)=2x^2-7

Explanation:

So we have the two functions:


f(x)=x^2-1\text{ and } g(x)=2x-5

And we want to find:


(g\circ f)(x)

This is the same as:


=g(f(x))

So, substitute f(x) into g(x). Thus:


g(x)=2x-5\\g(f(x))=2(x^2-1)-5

Distribute the 2:


g(f(x))=2x^2-2-5

Subtract:


g(f(x))=2x^2-7

Therefore:


(g\circ f)(x)=2x^2-7

And we're done!

User Maana
by
5.8k points